Cooperative Practices - Andl, Helga; Trendl, Fanni; Varga, Aranka (Autonomy and Responsibility Journal of Educational Sciences, 2022)
Our study records the results of a research that focuses on the practical implementation of cooperative learning, in correlation to a university course held for practising teachers. The survey concerning this topic took place in 2015 and 2017 (N=114). This research corrobo rated our recent fi ndings from 2013: theoretical and practical knowledge acquired in the course, as well as the opportunity to plan and test a cooperative task or lesson through out the course – that was centred around the pedagogues’ own experiences and horizontal learning - has signifi cantly affected the attitude towards cooperative learning-organisation of those teachers who have attended regularly. The obvioussi milarity of these results refl ect that the contextual changes in the educational fi eld do not alter the finding swhich clearly show that experiential learning based on cooperative principles helps create a learning environment of high quality on the many levels of formal education.